Cladosporium species from submerged decayed leaves in Brazil, including a new species and new records - Freitas, Mayara L. R.; Gomes, André A. M.; Rosado, André W. C.; Pereira, Olinto L. (Phytotaxa, 2021)
Fungi belonging to the genus Cladosporium are cosmopolitan and occur in various substrates and hosts. Nevertheless, this is the first time that we have described this genus colonizing leaf litter submerged in water. We surveyed Cladosporium spp. associated with submerged leaf litter, from three localities belonging to the Atlantic Forest biome in the State of Minas Gerais, Brazil. A multilocus DNA sequence typing approach employing ITS, Actin, and Translation elongation factor 1-α region/genes associated with morphological and cultural analyses were used to identify these species. The species C. angulosum and C. anthropophilum are reported for the first time in Brazil, and a new species for the genus is described here as C. puris.